The contribution of increased global soil salinity to changes in inorganic carbon - Xiaofang Jiang; Xian Xue (Proceedings of the National Academy of Sciences, 2026)
Soil salinization poses a serious environmental challenge, but the impact of global salinity on SIC (Soil Inorganic Carbon) remains unclear. Using 94,515 samples from 0 to 200 cm depth, combined with subregional classification (such as soil type, land use, climate, geomorphology, and soil texture) which helps address spatial heterogeneity, we obtain relatively accurate global distribution data for EC (Electrical Conductivity) and SIC. EC of 0 to 40 cm layer positively influences SIC in most taxonomic subregions, which may be due to the inorganic CO 2 absorption influenced by pH and salinity. EC of 80 to 100 cm layer sometimes negatively influences SIC due to the increase of soil depth. When EC is below 4 dS/m, EC often positively influences SIC. When EC increases by 2 to 4 dS/m, the mean global SIC in 0 to 20, 20 to 40, and 80 to 100 cm layers increases from 66.15, 78.75, and 117.39 to 174.47 to 190.38, 132.76 to 154.98, and 149.14 to 161.37 g/kg, respectively. The increase is relatively high but similar overall, which deserves high attention. These findings elucidate the dynamics of carbon–salt coupling in the soil–atmosphere–water system, offering pivotal scientific insights for carbon-neutrality strategies.